A STUDY OF FIGURATIVE LANGUAGE FOUND IN WESTLIFE’S SONGS ON COAST TO COAST ALBUM - SUGIYANTO, EKA NUR NOVIANI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Sugiyanto, Eka Nur Noviani. 2013. A Study of Figurative Language Found in Westlife’s Songs on  Coast to Coast  Album.  Study Program of English, Universitas Brawijaya. Supervisor : Ismarita Ida; Co  –  Supervisor : Emy Sudarwati. Keywords : Stylistics, Figurative Language, Westlife’s Coast to Coast Album. This research deals with figurative language employed in Westlife’s songs on Coast to Coast album. There are two problems to answer in the analysis. First is what figurative languages are found in Westlife’s songs on  Coast to Coast album. For the second one is what are the messages of the songs in Westlife’s songs on Coast to Coast album.  This study uses qualitative approach. The data sources used in this study are the lyrics of the 19 songs of Westlife boyband on Coast to Coast album. This study uses the theory of figurative language by Keraf (1991) and Perrine (1969).  The result reveals that there are 163 figurative languages found in Westlife’s songs on Coast to Coast album. Those figurative languages are divided into 2 similes, 89 metaphors, 27 personifications, 5 ironies, 1 allusion, 8 synecdoches, 31 hyperboles and there is no metonymy at all. Figurative language that is mostly used in this album is metaphor. The songwriter uses the figurative language itself to add some elegance to the song. There are also its messages of each song that was shown by the used of figurative language.  The writer hopes that the future writers understand the theory of stylistics, especially about figurative language and its meaning to understand what is the contents of the song and also its messages. Second is they could use another theory to make their study different from the writer. Third, if they want to conduct a study that is related to the written media, they should decide the object well so it will not make any trouble when the study is going on.